Si ven a alguien vivo. Crónicas III - Alzate, Gabriel Jaime (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2011)
The phrase "if you see someone alive, tell them the same", left her scarred. Jenny could not imagine seeing her comrades dead, those with whom she had shared part of her life. The lieutenants had died and several of their comrades had fallen with them. Jenny and Maritza ran as they had never run before. They didn't care about anything. "But this image will never be erased from my mind: in the middle of the run we made, Yuli, one of our youngest comrades, only eight years old, was coming up with her arm shattered and begging not to be left to die. But she didn't even finish these words when one of those guerrilla sons of bitches shot her in the back. Maritza and I were paralyzed; there was nothing left of the race we had been running, only the mere agitation of breathing. I thought, then, that my moment had come. Those were the longest seconds of my life. All I could think about was my mother, how she would be, if she would have found out what was happening, because in a small town everything is known" (Fragment of a chronicle).